Stochastic dominance and information value - KWON, Young Koan (Institutional Knowledge at Singapore Management University, 1979)
Incentives for producing and disseminating information have been analysed in many different contexts. Kihlstrom [6], for example, develops a Bayesian framework to analyze the properties of demand functions for information about product quality. From an entirely different perspective, Spence [8, 91 demonstrates the private value of “signalling” information. Similarly, Wilson [lo] considers the value to the firm of producing technological information and the effect of such production on equilibrium theory.